IMPACT OF POLICY MEASURES OF PAKISTAN IN COVID-19 PANDEMIC - Sabeen Azam (International Conference on Social and Islamic Studies, 2021)
The Covid-19 pandemic has been hitting the globe. Almost every country is affected by this pandemic. The coronavirus epidemic has had a significant influence on Pakistan's economic activities as well as the loss of human life. With a few notable exceptions, almost all industries have been negatively impacted as domestic demand and exports have sharply decreased, with few notable exceptions where high growth has been witnessed. This study examines how the public health issue has impacted Pakistan’s most important economic sectors. While the government has put in place certain mitigating measures, they are insufficient to combat the pandemic's effects. The study examines how the Pakistani economy might affect the country's hybrid political structure, which is dominated by the elites. An attempt is made to assess the impact and potential remedies for a few significant industries. The impact and policy measures need to be more pro-active to be effect and implicated on ground measures.